2012
DOI: 10.3329/jhpn.v30i1.11271
|View full text |Cite
|
Sign up to set email alerts
|

Storing Drinking-water in Copper pots Kills Contaminating Diarrhoeagenic Bacteria

Abstract: Microbially-unsafe water is still a major concern in most developing countries. Although many water-purification methods exist, these are expensive and beyond the reach of many people, especially in rural areas. Ayurveda recommends the use of copper for storing drinking-water. Therefore, the objective of this study was to evaluate the effect of copper pot on microbially-contaminated drinking-water. The antibacterial effect of copper pot against important diarrhoeagenic bacteria, including Vibrio cholerae O1, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Although many studies have shown the antimicrobial effects of copper surfaces in hospitals, the use of copper in drinking water treatment, has been limited to silver-copper ionization systems for the control of Legionnaire’s disease (Stout and Yu, 2003) and copper pots in developing countries (Sudha, 2012). At the material cost of only a few cents per filter, one sheet of CuNP paper can be synthesized in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many studies have shown the antimicrobial effects of copper surfaces in hospitals, the use of copper in drinking water treatment, has been limited to silver-copper ionization systems for the control of Legionnaire’s disease (Stout and Yu, 2003) and copper pots in developing countries (Sudha, 2012). At the material cost of only a few cents per filter, one sheet of CuNP paper can be synthesized in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, for POU applications, we have designed a paper sheet embedded with silver nanoparticles to purify drinking water contaminated with bacteria (Dankovich and Gray, 2011a; Dankovich, 2014). As a more affordable alternative to silver, researchers have turned to using copper to purify drinking water (Sudha et al, 2012; Stout and Yu, 2003; Varkey and Dlamini, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudha et al, (2009) reported that water stored overnight in copper pots gave no counts for E. coli, S. typhi and V. cholerae, demonstrating inactivation of these bacteria. Sudha et al (2012) Use of copper in history is found to be about 10,000 years ago. In 3000 B.C., copper ores were found in the island of Cyprus.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action of copper on bacteria is not completely understood (Sudha et al, 2012). Some studies conclude that the copper ions brought about complete killing of bacteria by membrane damage (Santo et al, 2011).…”
Section: Resultsmentioning
confidence: 99%